Single‐ vs Double‐Decker Copper 12‐MC‐4 Metallacrown Using the Coordination Flexibility of a Soft Donor Ligand. Issue 22 (14th June 2022) - Gamer, Christoph; Sundaresan, Sriram; Carrella, Luca M.; Rentschler, Eva
Abstract: 2‐Methylmercaptobenzohydroxamic acid (mmbHA ) has been synthesized and used to form Cu II Cl2 (MeOH)[12‐MCCu(II)N(mmbHA) ‐4]2 ⋅ 4MeOH (1 ) and Cu II (μ2 ‐ClO4 )(MeOH)2 (py)4 [12‐MCCu(II)N(mmbHA) ‐4]ClO4 (2 ), a copper(II) based double‐decker and a discrete metallacrown (MC) system, respectively. While 1 forms in the absence of a coordinating co‐ligand, the presence of pyridine (Py) leads to a change in the coordination mode of mmbHA and a discrete MC 2 is formed. Both compounds have been structurally and magnetically characterized. The magnetic susceptibility measured from 2–300 K shows overall antiferromagnetic exchange coupling within both crown structures and the obtained coupling constants are J1 =−88.0(1) cm −1 and J2 =−64.7(3) cm −1 for 1 and J1 =−90.0(5) cm −1 and J2 =−31.1(1) cm −1 for 2 . However, the ratio of the coupling parameters is highly affected by the structural change. Abstract : A methylmercaptobenzo hydroxamic acid (mmbHA ) ligand has been synthesized, which is suitable to form 12‐metallacrown (MC)‐4 structures. Two distinct copper(II) based MC systems were synthesized and structurally analyzed. The use of pyridine as co‐ligand led to a drastic change of the mmbHA coordination mode and thus to the formation of a discrete MC in the case of 2, whereas a double‐decker structure is formed in compound 1 . The magnetic susceptibility measured from 2–300 K shows overall antiferromagnetic exchange coupling within both crown structures.